The Heterogeneity of Firms Behavior at Oligopolistic Market: Price-makers and Price-takers - A.Yu. Filatov (Известия Иркутского государственного университета: Серия "Математика", 2015)
The paper considers the model of strategic interaction of firms at the quantity oligopoly market. There are several price-makers maximizing profits using the Cournot strategy, and also several price-takers obtaining outputs from the equivalence of price and marginal costs. The second strategy can be used due to some rational reasons, for example, unavailability of demand function, and competitors’ cost functions essential for reaction curves construction, or due to misunderstanding of its own market power and influence on the equilibrium parameters. Myopic behavior decreases profits comparing to Cournot firms if occurs unilaterally. But the competitors will adapt, and it can unexpectedly make the second strategy effective. The paper analyses the case of linear demand and symmetric firms with quadratic costs. It’s shown that prace-takers’ output is even greater than the output of the Stackelberg leader. The profit can be greater or lower than the original price-makers profits. It depends on the market parameters include the price elasticity of demand and the rate of marginal costs increasing. It’s shown that the probability for price-taker strategy to be efficient is not big, but increases at a large market with inelastic demand and many firms with slowly increasing marginal costs. It’s better for price-taker to be the only one firm with such a strategy.